2013
DOI: 10.1371/journal.pone.0072858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipid-Lowering Drugs on Irisin in Human Subjects In Vivo and in Human Skeletal Muscle Cells Ex Vivo

Abstract: Context and ObjectiveThe myokine irisin has been proposed to regulate energy homeostasis. Little is known about its association with metabolic parameters and especially with parameters influencing pathways of lipid metabolism. In the context of a clinical trial, an exploratory post hoc analysis has been performed in healthy subjects to determine whether simvastatin and/or ezetimibe influence serum irisin levels. The direct effects of simvastatin on irisin were also examined in primary human skeletal muscle cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 48 publications
10
60
1
1
Order By: Relevance
“…Gouni-Berthold and cols. also examined the relationship between irisin levels and TFT on 72 male patients, who used lipid-lowering medicine, and found no statistically significant relationship either in the groups or in the whole population (19). The results of their study are in consistence with our results since their study was performed with patients without euthyroid or another documented thyroid disease.…”
Section: Discussionsupporting
confidence: 69%
“…Gouni-Berthold and cols. also examined the relationship between irisin levels and TFT on 72 male patients, who used lipid-lowering medicine, and found no statistically significant relationship either in the groups or in the whole population (19). The results of their study are in consistence with our results since their study was performed with patients without euthyroid or another documented thyroid disease.…”
Section: Discussionsupporting
confidence: 69%
“…Recent data has revealed that lipid-lowering drugs affect circulating irisin levels in humans and PIs increase HDL cholesterol levels in women infected with HIV (26). In this sense, women presented longer infection and HAART durations when compared with men, although this finding was not significant, while a poor correlation between HAART and irisin levels was observed.…”
Section: Discussionmentioning
confidence: 91%
“…In our study, irisin concentrations were more likely to be lower in overweight and obese children compared to normal-weight children, and irisin exhibited a significant inverse correlation with BMI SDS in all the children in this study. Studies have reported that irisin is related to BMI; however, irisin was not significantly correlated with BMI in other studies [23,24]. The circulating irisin levels have been shown to be negatively correlated with BMI [25][26][27], whereas some reports suggested that irisin concentrations were positively associated with BMI [20,28].…”
Section: Discussionmentioning
confidence: 91%